U-Pb SIMS zircon ages for Cambro-Ordovician rocks, Valongo Anticline, northwestern Portugal - Brookfield, Michael E.; Couto, Helena; Catlos, Elizabeth J.; Schmitt, Axel (Journal of Mediterranean Earth Sciences, 2021)
Zircons in three samples of the Cambrian Montalto Formation and “Tremadoc-Arenig Santa Justa Formation of the Valongo Anticline in northwest Portugal were dated by U-Pb secondary ion mass spectrometry (SIMS). A rhyolite sample near the top of the Montalto Formation gave clusters of Lower Paleozoic (600 to 450 Ma) and Upper Carboniferous zircon ages (360 to 300 Ma), with one Paleoproterozoic age (~1750 Ma). The middle black chert sample, underlying the massive “Arenig” quartzites of the Santa Justa Formation, gave only two zircon ages of 827 Ma and 492 Ma. The uppermost volcanic sandstone, overlying the massive “Arenig” quartzites of the Santa Justa Formation, gave similar zircon ages to the lowermost sample, but with mostly Neoproterozoic ages (933 to 560 Ma). The youngest Upper Carboniferous age clusters are caused by zircon alteration or hydrothermal recrystallization during Variscan metamorphism. The oldest Neoproterozoic ages are detrital and represent erosion of regional basement. The Lower Paleozoic ages are also mostly detrital but are from zircons eroded from underlying lavas and volcaniclastics associated with the rifting that preceded the opening of the Rheic ocean. The youngest concordant age of 516±16 Ma of the rhyolite may be the best age for the top of the Montalto Formation, which puts it as equivalent to Middle Cambrian Series 2. The other early Paleozoic zircon dates are all earlier Cambrian. The overlying samples give older ages suggesting progressive erosion of underlying rocks during rift shoulder uplift. A major period of volcanic activity occurred in the latest Cambrian to earliest Ordovician of northern Portugal, though this is poorly constrained by biostratigraphy. Our results, thoughlimited in number,indicate that only the upper quartzite part of the Santa Justa Formation can be equivalent to the so-called “Arenig” quartzites (also poorly constrained) in NW France and Iberia. The Upper Cambrian and Tremadocian seems to be missing in the studied area where a major unconformity probably occurs below the lower Santa Justa Formation.